2016
DOI: 10.1016/j.renene.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic anaerobic co-digestion feasibility study for two-phase olive oil mill pomace and pig slurry

Abstract: a b s t r a c tAnaerobic mono-(AmoD) and co-digestion (AcoD) of two-phase olive oil mill pomace (TPOP) and pig slurry (PS) at different ratios were studied in a semi-continuous stirred tank reactor (sCSTR) at mesophilic temperature (37 C). The methane yields for AcoD experiments ranged from 150.9 to 274.3 L CH 4 kg VS À1 d À1 . The maximum chemical oxygen demand (COD) removal rate (59.60%) was achieved for TPOP/PS 80:20 w/w substrate composition at OLR 3.68 g VS L reactor À1 d À1 and 24 days HRT. Despite the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 42 publications
(47 reference statements)
0
17
0
2
Order By: Relevance
“…However, numerous obstacles still need to be overcome such as growth inhibition of methanogenic archaea by phenolic compounds, low pH, low nitrogen concentration, etc. (Orive et al, 2016). Other biological alternatives are aerobic methods and include composting as well as treatments with fungi, bacteria, and algae (Pinto et al, 2003;Dhouib et al, 2006;Tziotzios et al, 2007;Chowdhury et al, 2013).…”
Section: Biological Treatments Of Omwwmentioning
confidence: 99%
“…However, numerous obstacles still need to be overcome such as growth inhibition of methanogenic archaea by phenolic compounds, low pH, low nitrogen concentration, etc. (Orive et al, 2016). Other biological alternatives are aerobic methods and include composting as well as treatments with fungi, bacteria, and algae (Pinto et al, 2003;Dhouib et al, 2006;Tziotzios et al, 2007;Chowdhury et al, 2013).…”
Section: Biological Treatments Of Omwwmentioning
confidence: 99%
“…Co‐digestion has been proven to increase productivity because of a favorable balance of nutrients . Based on the experimental results obtained in a semi‐continuous stirred tank reactor, the authors concluded that positive net present values (NPVs), an internal rate of return higher than the discount rate and relatively short payback periods can be attained . In another work on anaerobic digestion using olive pomace and olive waste water, an Energy Sustainability Index was calculated as the ratio between the energy produced and spent to produce chemical products used in several pre‐treatment processes that olive residues were submitted to before anaerobic digestion.…”
Section: Research On Different Types Of Olive‐derived Biomassesmentioning
confidence: 99%
“…Bununla birlikte, asidik bir pH değerine sahip olması, düşük alkalinite, düşük azot içeriği, zeytin çekirdeği ve meyvesinin işlenmesi neticesinde oluşan fenolik bileşikler ve lipit fraksiyonlarının varlığı gibi çeşitli ZK özellikleri, bu atıksuyu potansiyel toksik bir substrat haline getirir ve sonuç olarak bu durum anaerobik biyosistem için uygun değildir. Bu sorunların üstesinden gelmek için çeşitli sentetik besin maddeleri, kimyasal ilaveler ve su ile seyreltilmesinin yanı sıra ön işlem uygulamalarının (kimyasal ve biyokimyasal) ZK'nın anaerobik olarak arıtılmasını mümkün kıldığı bildirilmiştir [31,32,[36][37][38][39]. Bununla birlikte, ön arıtma işlemleri genellikle metanojenik aktiviteyi yavaşlattığı bilinmekte ve arıtma maliyetlerinin artmasına sebep olmaktadır [39].…”
Section: Introductionunclassified